2015
DOI: 10.1103/physrevb.91.075207
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioelectronic structure, optical, and magneto-optical properties of MnGaAs digital ferromagnetic heterostructures

Abstract: We report on a theoretical study of the electronic, optical, and magneto-optical properties of digital ferromagnetic heterostructures based on Mn δ-doped GaAs. We consider different structures corresponding to Mn contents within the range 12%-50% and we study how the system changes as a function of the doping concentration. Our first-principles approach includes the spin-orbit interaction in a fully relativistic pseudopotential scheme and the local-field effect in the description of the optical absorption. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Previous theoretical works on GaAs 1−x P x layers has been shown that the energy-band gap (Eg) increased with increasing P doping [34]. The blue shift identified between the studied layers was also observed in theoretical and experimental previous works as a function of Mn and P doping [32,35,36]. Indeed, Yahyaoui et al highlighted the enhancement of Eg as a function of P doping in (Ga, Mn)(As, P) layers [37].…”
Section: Resultssupporting
confidence: 59%
“…Previous theoretical works on GaAs 1−x P x layers has been shown that the energy-band gap (Eg) increased with increasing P doping [34]. The blue shift identified between the studied layers was also observed in theoretical and experimental previous works as a function of Mn and P doping [32,35,36]. Indeed, Yahyaoui et al highlighted the enhancement of Eg as a function of P doping in (Ga, Mn)(As, P) layers [37].…”
Section: Resultssupporting
confidence: 59%
“…Kim et al 18 focused on the surface effect and structural dependence of the MOKE spectra in Co thin films and CoPt alloys, and Stroppa et al 19 analyzed the electronic structure and magneto-optical property of uniformly Mn-doped GaAs. Very recently, Rosa et al 20 also performed the study of the magneto-optical property of Mndoped GaAs in a special digital ferromagnetic heterostructure. Moreover, Ravindran et al 21 investigated the magnetic, optical, and magneto-optical properties of manganese pnictides and found a systematic increase of the Kerr rotation angles from MnAs, to MnSb, and to MnBi.…”
Section: Introductionmentioning
confidence: 99%
“…Although MOKE experiments have been almost always conducted on various types of ferromagnets in the past [14][15][16][17][18][19][20][21][22][23][24] , no explicit conclusion has been established that MOKE must be absent when either magnetization or SOC is not present. In particular, whether MOKE can arise from a spin nonpolarized system (without magnetization) or not is still an open question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evaluation of magneto-optical spectrum of iron from first principles was performed by Singh et al 24 followed by Oppeneer et al 25 evaluating the Kerr rotation spectra of bcc Fe. The rise of the ab initio codes in recent decades have enabled to model the MO spectra for real materials 26 , 27 and it has quickly become a common practice in research 28 33 . The ab initio codes also opened up new possibilities in the investigations of the microscopic origins of the MO effect that go beyond the semiclassical models 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%